Stanniocalcin-1 Hormone in Nonpreeclamptic and Preeclamptic Pregnancy: Clinical, Life-Style, and Genetic Modulators - Juhanson, Peeter (J Clin Endocrinol Metab, 2016)
CONTEXT AND OBJECTIVES: The study represents the first comprehensive analysis of Stanniocalcin-1 (STC1) hormone in human pregnancy, assessing clinical, lifestyle, and genetic determinants of circulating STC1 at term. DESIGN, SETTING, AND PARTICIPANTS: Participants included women with (n = 50) and without (n = 316) preeclampsia (PE) at delivery, recruited in the REPROgrammed fetal and/or maternal METAbolism (REPROMETA) study (2006–2011, Estonia). Genetic association analysis combined PE cases (n = 597) and controls (n = 623) from the REPROMETA and Finnish Genetics of Preeclampsia Consortium (2008–2011) studies. MAIN OUTCOME MEASURE(S): Maternal postpartum plasma STC1 was measured by ELISA (n = 366) and placental STC1 gene expression by TaqMan quantitative RT-PCR (n = 120). Genotyping was performed using Sequenom MassArray. RESULTS: Significantly higher STC1 plasma level was measured for the PE (median, 1952 pg/mL; 1030–4284 pg/mL) compared with non-PE group (median, 1562 pg/mL; 423–3781 pg/mL; P = 3.7 × 10(−4), Mann-Whitney U test). Statistical significance was enhanced after adjustment for cofactors (linear regression, P = 1.8 × 10(−6)). STC1 measurements were negatively correlated with maternal smoking. Prepregnancy body mass index had a positive correlation with STC1 only among PE patients (r = 0.45; P = .001). The strongest genetic association with hormone concentrations was detected for STC1 single nucleotide polymorphisms rs3758089 (C allele: minor allele frequency, 5%; linear regression: β = 249.2 pg/mL; P = .014) and rs12678447 (G allele: minor allele frequency, 7%; β = 147.0 pg/mL; P = .082). rs12678447 placental genotypes were significantly associated with STC1 gene expression (P = .014). The REPROMETA/Finnish Genetics of Preeclampsia Consortium meta-analysis suggested an increased risk to develop late-onset PE for the rs12678447 G allele carriers (P = .05; odds ratio = 1.38 [0.98–1.93]). CONCLUSIONS: Increased STC1 hormone represents a hallmark of late-onset PE. STC1 gene variants modulate placental gene expression and maternal hormone levels.